Pulchinenosides: Correlation of surface activity-cytotoxicity and hepatocyte apoptosis mechanism study. (1st July 2021) - Su, Dan; Wang, Tingting; Jin, Chen; Liu, Yali; Naeem, Abid; Liao, Zhou; Zhou, Mingyue; Chen, Changlian; Song, Yonggui; Ai, Zhifu
Graphical abstract: Abstract: Saponin is an active component of many phytomedicine, which has extensive pharmacology effects. Meanwhile, it is reported that cytotoxicity, especially hemolysis and hepatotoxicity, in pentacyclic triterpenoid saponin (PTS) hindered their further development and application. Surface activity, a unique physical property of saponins, is believed to be related to membrane toxicity. However, the correlation between the surface activity and cytotoxicity of saponins is still unexplained. In this paper, our aim was to explore the relationship between surface activity-cytotoxicity of pulchinenosides and the hepatotoxicity mechanism of PTS in vitro. The surface activity of different saponins was investigated by contact angle, surface free energy (SFE), and oil/water partition coefficient (log Papp). In the cytotoxicity study, the hemolysis and hepatotoxicity activity of different saponins was compared by HD50 of erythrocyte and MTT, flow cytometry and LDH assay in LO2 cells respectively. And in the hepatotoxicity mechanism study, western blot was used for observing the expression of proteins related to apoptosis and exploring the liver injury mechanism of PTS. The results suggested that the influences of surface activity on hepatocytes and erythrocytes were different, indicating that the correlation of surface activity-cytotoxicity could provide more information for development of PTS. And the result of hepatotoxicity mechanism study of saponins suggested that endogenous and exogenous apoptotic pathways could be the potential targets of PTS, which could not only provide basis for clinical monitoring and treatment of the toxicity in saponins, but also provide more reference for the clinical application of PTS and phytomedicine containing PTS.